The fantastic Gustave Doré - Doré, Gustave (Prestel, 2023)
"If you were a consumer of literature in the nineteenth century, chances are the volumes in your library featured the illustrations of Gustave Doré. From the Bible to Shakespeare, Balzac to Milton, Cervantes to Poe, Doré's intricate, romantic, and exuberant drawings brought great works to life, and were as treasured as the stories and poetry they depicted. Furthermore, as this magnificent book reveals, he was also a skilled sculptor, painter, and cartoonist. This book spans Doré's entire career, with chapters dedicated to specific works such as The Divine Comedy, Don Quixote, Tennyson's Idylls of the King, and medieval fairy tales--each featuring exquisite full-page reproductions that allow Doré's genius for line, shading, and texture to shine through. The authors also provide a background on the techniques that Doré employed to achieve his exquisite works."--Amazon.com